PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIE MTs MADINATUN NAJAH RENGAT - Meldha Rizkiani; Rini Dian Anggraini; Zuhri Zuhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve learning process and increase student’s mathematical achievement through implementation of Discovery Learning model. This type of research is Classroom Action Research with two cycle. The research was conducted in class VIIIE Islamic Junior High School Madinatun Najah Rengat in the first semester of the 2018/2019 academic year. The subject of this research consist of 30 students, there are 14 female students and 16 male students. The research instrument consists of learning materials and instruments for collecting data. Learning materials used in this research are the Syllabus, Lesson Plan and Activity Sheets. Instrument data collectors used in this research are observation sheet and mathematical achievement test. Data analysis techniques in this study are descriptive narrative analysis of qualitative data and descriptive statistics analysis ofquantitative data. Based on analysis of the observation sheet, the application of Discovery Learning model can improve the learning process as indicated by the increase in the activity of teacher and student in each cycle. Data optained from mathematical achievement test result the percentage of students which ispass Minimum Mastery Crieria (MMC) increase from 36,7% to 53,3% at the first test and to 76,7% at the second test. This research concludes that the implementation of Discovery Learning model improved the learning process and the student’s mathematical achievement at class VIIIE Islamic Junior High School Madinatun Najah Rengat in the first semester of the 2018/2019 academic year.Key Words : Mathematics Learning Achievement, Discovery Learning Model, Classroom Action Research